2019
DOI: 10.1177/1937586719834729
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Design on Team Interactions Across Three Family Medicine Clinics: Perceptions of Communication, Efficiency, and Privacy

Abstract: Objective: In this study, we explored how two different primary care clinic physical layouts (onstage/offstage and pod-based [PB] designs) influenced pre- and postvisit team experiences and perceptions. Background: Protocols encourage healthcare team communication before and after primary care visits to support better patient care. Physical clinic environments may influence these behaviors, but limited research has been performed. Method: We conducted observations, three interviews with clinic managers, and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…Direct observation of human behavior reveals insights not accessible from other data collection methods such as self-report (Mays & Pope, 1995). The findings align with previous hospital-based and primary care research showing design factors having an important impact on staff collaboration (Gharaveis et al, 2018; Gunn et al, 2015; Karp et al, 2019; Rashid, 2009). By adopting a circulation/destination/transition zone space categorization, similar to others, we were able to identify design features that facilitate frequent on-the-fly communication (Gunn et al, 2015; Karp et al, 2019; Lyson et al, 2019; Oandasan et al, 2009) and suggest specific features of New Zealand primary care practice design associated with frequent informal staff communication.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Direct observation of human behavior reveals insights not accessible from other data collection methods such as self-report (Mays & Pope, 1995). The findings align with previous hospital-based and primary care research showing design factors having an important impact on staff collaboration (Gharaveis et al, 2018; Gunn et al, 2015; Karp et al, 2019; Rashid, 2009). By adopting a circulation/destination/transition zone space categorization, similar to others, we were able to identify design features that facilitate frequent on-the-fly communication (Gunn et al, 2015; Karp et al, 2019; Lyson et al, 2019; Oandasan et al, 2009) and suggest specific features of New Zealand primary care practice design associated with frequent informal staff communication.…”
Section: Discussionsupporting
confidence: 89%
“…The findings align with previous hospital-based and primary care research showing design factors having an important impact on staff collaboration (Gharaveis et al, 2018;Gunn et al, 2015;Karp et al, 2019;Rashid, 2009). By adopting a circulation/destination/transition zone space categorization, similar to others, we were able to identify design features that facilitate frequent on-the-fly communication (Gunn et al, 2015;Karp et al, 2019;Lyson et al, 2019;Oandasan et al, 2009) and suggest specific features of New Zealand primary care practice design associated with frequent informal staff communication. The importance of informal, face-to-face, onthe-fly communication facilitated through the interior architecture for developing collaborative primary care teams both extends and is consistent with Egan & Jaye's (2009) community of clinical practice concept.…”
Section: Discussionsupporting
confidence: 84%
“…While openness of team areas was associated with lower teamwork perception by patients, the openness of staff work areas to patients may support patient experiences by allowing more encounters with staff members as Karp et al (2019) described. During our observations, multiple interactions between patients and staff members were observed as a result of staff-patient visual relationships.…”
Section: Openness Of Team Area and Staff-patient Encountersmentioning
confidence: 92%
“…Freihoefer et al (2017) reported more frequent communication in an onstage/offstage clinic layout that separates patients from staff compared to the clinic layout with exposed staff work areas. Karp et al (2019) observed more frequent communication within the care team in the onstage/offstage clinic layout compared to the pod-based clinic layout with private provider offices.…”
Section: Introductionmentioning
confidence: 87%